The place of autodermaplasty in today's medicine (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Today, as a result of various physical injuries, damage to the external protective part of the body (skin) is observed. In these cases, the patient's damaged skin is replaced with a new one or skin is transplanted from another part of the body. Autodermaplasty is the implementation of this process and  provides information about this process.